A Simple and Precise Procedure for a Complete Characterization of a Cone-Beam Computed Tomography System - Kun-Long Shih; Shih-Chun Jin; Chia-Wei Wang; Jyh-Cheng Chen (Sensors)
In the calibration of cone-beam computed tomography (CBCT), two factors must be checked: the alignment of the imaging detector of the CBCT system and the effect of the slanted sample platform. Previously, we developed and validated a distinct procedure to accurately calibrate any misalignment of the detector by using a cylindrical phantom with beads in a straight line, parallel to the axis of rotation of the CBCT system. Here, we generalize our earlier procedure to calibrate the CBCT system while also detecting and rectifying a slight slant of the sample platform. We revise and validate our new procedure by calibrating the CBCT system, which also determines the tilt angle between the central axis of the phantom and the axis of rotation, when not 0°. The errors in misaligned angles for our new procedure are within ±0.03°, calibrating the CBCT system more precisely than our earlier work. To confirm this, we have performed a complete, precise calibration of a dental CBCT system with a tilting sample platform. We also reconstruct a HA phantom in this CBCT system to analyze the quality of reconstruction. We present here a validated method for calibrating a CBCT system and rectifying the effect of its tilting sample platform with good accuracy.